Financing municipal projects in upper Denkyira east municipal assembly: A comparison of build-operate- transfer and traditional procurement methods. - DODOU, RICHMOND (KNUST, 2025)
A Thesis Submitted To The Department Of Accounting And Finance In Partial Fulfillment Of The Requirements For The Degree Of Master Of Business Administration (Finance).